Numérique et apprentissages : prescriptions, conceptions et normes d'usage - Georges Ferone (Nantes Université, 2019)
We seek to identify standards able to inform professional practice with regard to technology-assisted learning by studying future teacher's conceptions of the matter. A case study shows that students teachers of the ESPE Créteil and teachers have similar perceptions. Both groups consider that digital technologies can promote learning and autonomy as it is fun and motivating, but is also an obstacle to the development of reading and writing proficiency. These conceptions, marked by doxas, reveal an attempt to compromise between new societal and institutional standards that are very favorable to digital technologies and traditional norms of the job. Thus, student teachers contrast the book with the screen and the pen with the keyboard. This study highlights the need to address these developing conceptions in order to create new standards for the use of digital educational technologies.